Natural products from Cuscuta reflexa Roxb. with antiproliferation activities in HCT116 colorectal cell lines. Issue 5 (4th March 2017) - Riaz, Muhammad; Bilal, Aishah; Ali, Muhammad Shaiq; Fatima, Itrat; Faisal, Amir; Sherkheli, Muhammad Azhar; Asghar, Adnan
Abstract: Parasitic Cuscuta reflexa Roxb . possesses many medicinal properties and is a rich source of a variety of biologically relevant natural products. Natural products are the prime source of leads, drugs, and drug templates, and many of the anticancer and antiviral drugs are either based on natural product or derived from them. Cancer is a devastating disease and one of the leading causes of death worldwide despite improvements in patient survival during the past 50 years; new and improved treatments for cancer are therefore actively sought. Colorectal cancer is the fourth most prevalent cancer worldwide and is responsible for nearly 9% of all cancer deaths. Our search for anticancer natural products from C. reflexa has yielded four natural products: Scoparone (1 ), p -coumaric acid (2 ), stigmasta-3, 5-diene (3 ) and 1- O - p -hydroxycinnamoylglucose (4 ) and among them 1- O - p -hydroxycinnamoyldlucose (4 ) showed promising antiproliferative activities in HCT116 colorectal cell lines, whereas compounds1 –3 showed moderate activities. Abstract :